2016
DOI: 10.21606/drs.2016.191
|View full text |Cite
|
Sign up to set email alerts
|

From Participation to Collaboration: Reflections on the co - creation of innovative business ideas

Abstract: Design-led innovation interventions are predicated on the importance of establishing complex disciplinary collaborations. This paper reflects on the effects of different co-design methods to support knowledge exchange and the co-creation of new business ideas with multidisciplinary participants. It draws on data collected from sandpit style events entitled Chiasma, undertaken as part of the knowledge exchange hub, Design in Action (DiA) in which co-design methods were used to bring designers, entrepreneurs, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Based on the thematic analysis carried out by Broadley et al (2016), authors argue that nuanced range of tools, techniques and methods can strengthen the multidisciplinary engagement and can create a shift from co-design methods to sustain collaborative mindsets in knowledge swap toward innovation. When innovation is in question, cross-boundary teaming is viewed as an increasingly popular strategy for innovation.…”
Section: Knowledge Transfer Between Project Team Membersmentioning
confidence: 99%
“…Based on the thematic analysis carried out by Broadley et al (2016), authors argue that nuanced range of tools, techniques and methods can strengthen the multidisciplinary engagement and can create a shift from co-design methods to sustain collaborative mindsets in knowledge swap toward innovation. When innovation is in question, cross-boundary teaming is viewed as an increasingly popular strategy for innovation.…”
Section: Knowledge Transfer Between Project Team Membersmentioning
confidence: 99%
“…Hand-in-hand with a multidisciplinary approach, the authors advocate an inclusive process, where stakeholders are actively involved as experts during problem framing and co-creation activities (Broadley et al, 2016;Björgvinsson, Ehn, & Hillgren, 2010). Co-creation is a broad term, but can be defined as two or more people working creatively in collaboration (Sanders & Stappers, 2008).…”
Section: Context: a Design-led Approach To Facilitation Co-creation mentioning
confidence: 99%
“…Munoz et al (2014) concede that in more remote areas participation rates are observed to be stronger and opportunities to develop innovative approaches to alleviate barriers to service production tend to be more profuse, thus suggesting that 'different strategies might be required to mobilize coproducers in different settings ' (2014: 219). We maintain that in order to embark on codesign activities authentically and with integrity, design researchers must first develop responsive and resonant ways to stimulate engagement and support participation (Broadley et al, 2016), for it is only through transcending these necessary acts that contextual understandings are constructed, issues are surfaced, relationships are formed, skills and capabilities are realized, a culture of imagination and experimentation is fostered, and the foundations are laid for developing effective design interventions together.…”
Section: Remote and Direct Approaches To Strengthen And Sustain Ownermentioning
confidence: 99%